PEMANFAATAN MEDIA INTERAKTIF DI SEKOLAH DASAR KELAS IV DI KECAMATAN BANJARBARU SELATAN: Upaya Meningkatkan Keterlibatan Siswa dalam Pembelajaran Pendidikan Jasmani - Ritonga, Thomas Hidayat; Rakhman, Arie; Indah , Eka Purnama (Jurnal Porkes, 2025)
This study aims to determine students' interest in using interactive media in PJOK learning and teachers' opinions about the use of interactive media. This study used a quantitative descriptive approach. The population of this study were teachers and 4th grade students of three elementary schools in South Banjarbaru District, The sample of this study consisted of 5 instructors and 94 students. The tool used was a questionnaire, and data was collected using a purposive sampling strategy. This study measured teachers' and students' responses to the interactive media using a questionnaire sheet with a 5-point Likert scale. The results of research on student interest in interactive media in the category strongly agree indicators of knowledge, category agree indicators of pleasure, interest, understanding, enthusiasm, activeness, help, ease, no difficulty, category less agree indicators less happy. The results of research on teacher responses to interactive media in the category strongly agree indicators of pleasure, and interest, category agree indicators of help, ease, enthusiasm, support, application, motivation, category disagree indicators of difficulty, category strongly disagree indicators of not interested. The knowledge indicator occupies a strongly agreed category of 47.87%, indicating that interactive media contributes to increasing student insight. Other indicators such as understanding 48.94%, interest 43.62%, convenience 42.55%, enthusiasm 36,